Blunt small bowel perforation (SBP): An Eastern Association for the Surgery of Trauma multicenter update 15 years later. Issue 4 (April 2019) - Fakhry, Samir M.; Allawi, Ahmed; Ferguson, Pamela L.; Michetti, Christopher P.; Newcomb, Anna B.; Liu, Chang; Brownstein, Michelle R.
Abstract : BACKGROUND: Previous work demonstrated diagnostic delays in blunt small bowel perforation (SBP) with increased mortality and inability of scans to reliably exclude the diagnosis. We conducted a follow-up multicenter study to determine if these challenges persist 15 years later. METHODS: We selected adult cases with blunt injury, International Classification of Diseases, Ninth Revision or current procedural terminology (CPT) indicating small bowel surgery, no other major injury and at least one abdominal computed tomography (CT) within initial 6 hours. Controls had blunt trauma with abdominal CT but not SBP. After institutional review board approval, data from each center were collected and analyzed. RESULTS: Data from 39 centers (from October 2013 to September 2015) showed 127, 919 trauma admissions and 94, 743 activations. Twenty-five centers were Level 1. Centers submitted 77 patients (mean age, 39; male, 68%; mean length of stay, 11.3 days) and 131 controls (mean age, 44; male, 64.9%; length of stay, 3.6 days). Small bowel perforation cases were 0.06% of admissions and 0.08% of activations. Mean time to surgery was 8.7 hours (median, 3.7 hours). Initial CT showed free air in 31 cases (43%) and none in controls. Initial CT was within normal in three cases (4.2%) and 84 controls (64%). Five cases had a second scan; two showed free air (one had an initial normal scan). One death occurred among the patients (mortality, 1.4%; and time to surgery, 16.9 hours). Regression analysis showed sex, abdominal tenderness, distention, peritonitis, bowel wall thickening, free fluid, and contrast extravasation were significantly associated with SBP. CONCLUSIONS: Blunt SBP remains relatively uncommon and continues to present a diagnostic challenge. Trauma centers have shortened time to surgery with decreased case mortality. Initial CT scans continue to miss a small number of cases with potentially serious consequences. We recommend (1) intraperitoneal abnormalities on CT scan should always evoke high suspicion and (2) strong consideration of additional diagnostic/therapeutic intervention by 8 hours after arrival in patients who continue to pose a clinical challenge. LEVEL OF EVIDENCE: Observational study, level III.